The development and validation of measures to assess cooking skills and food skills - Fiona Lavelle; Laura McGowan; Lynsey Hollywood; Dawn Surgenor; Amanda McCloat; Elaine Mooney; Martin Caraher; Monique Raats; Moira Dean (BMC, 2017)
Abstract Background With the increase use of convenience food and eating outside the home environment being linked to the obesity epidemic, the need to assess and monitor individuals cooking and food skills is key to help intervene where necessary to promote the usage of these skills. Therefore, this research aimed to develop and validate a measure for cooking skills and one for food skills, that are clearly described, relatable, user-friendly, suitable for different types of studies, and applicable across all sociodemographic levels. Methods Two measures were developed in light of the literature and expert opinion and piloted for clarity and ease of use. Following this, four studies were undertaken across different cohorts (including a sample of students, both 'Food preparation novices' and 'Experienced food preparers', and a nationally representative sample) to assess temporal stability, psychometrics, internal consistency reliability and construct validity of both measures. Analysis included T-tests, Pearson's correlations, factor analysis, and Cronbach's alphas, with a significance level of 0.05. Results Both measures were found to have a significant level of temporal stability (P < 0.001). Factor analysis revealed three factors with eigenvalues over 1, with two items in a third factor outside the two suggested measures. The internal consistency reliability for the cooking skills confidence measure ranged from 0.78 to 0.93 across all cohorts. The food skills confidence measure's Cronbach's alpha's ranged from 0.85 to 0.94. The two measures also showed a high discriminate validity as there were significant differences (P < 0.05 for cooking skills confidence and P < 0.01 for food skills confidence) between Food preparation novices' and 'Experienced food preparers.' Conclusions The cooking skills confidence measure and the food skills confidence measure have been shown to have a very satisfactory reliability, validity and are consistent over time. Their user-friendly applicability make both measures highly suitable for large scale cross-sectional, longitudinal and intervention studies to assess or monitor cooking and food skills levels and confidence.